Karnoprocesowa ochrona małoletniego pokrzywdzonego w sprawach o przestępstwa przeciwko wolności seksualnej i obyczajności — kilka uwag na tle nowelizacji wprowadzonej ustawą z dnia 13 czerwca 2013 r. o zmianie ustawy — Kodeks karny oraz ustawy — Kodeks postępowania karnego - Żylińska, Justyna (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
The article discusses issues linked with the protection of a minor victim in cases against sexual freedom and morality in the context of amendments introduced by the Act dated 13 June, 2013 Amending the Act — The Penal Code and the Act —The Criminal Procedure Code which took effect on 27 January, 2014 and introduced major amendments into the Criminal Procedure Code including the content of Art. 185a of the Criminal Procedure Code regulating the manner of examination of a minor victim who at the moment of the hearing is under 15 in proceedings concerning crimes referred to therein, among other things in the proceedings against sexual freedom and morality.Subject to analysis, particularly in the context of the aforesaid amendments, are the following issues:— scope of application of the regulations of Art. 185 a of The Criminal Procedure Code,— principle of single time examination of a minor victim in cases concerning crimes against sexual freedom and morality,— authority with a legal entitlement to interview a minor victim and other entities participating in the examination,— strategy for interviewing a minor victim in light of the Regulation of the Minister of Justice dated 18 December 2013 on the Preparation of the Interview Carried out in the Manner Referred to in Art. 185a–185c of the Criminal Procedure Code and the rules for recording the examination.
Keywords: ochrona małoletniej ofiary; przesłuchanie małoletniego; przestępstwa przeciwko wolności seksualnej i moralności; wtórna wiktymizacja